The Degree to Which Arabic Teachers in Kuwait Practice Their Various Classroom Roles - Al- Khawaldeh, Mohammed Ali; Al-Thafeeri, Abdulrahman Rakhees (Dirasat: Educational Sciences, 2023)
Objectives: The study aims at investigating the extent to which Arabic teachers in Kuwait carry out their various classroom roles. Methodology: The descriptive approach was followed by administering a classroom roles questionnaire, which included (23) categories divided into task-related, socio-affective, and technological roles. The study was conducted on (235) intermediate school Arabic teachers at Jahra governorate schools in Kuwait. Results: According to the findings of the study, teachers perform task-related and social-affective roles to a high degree and technological roles to a moderate degree. The findings also revealed a statistically significant difference in their practicing degree of socio-emotional roles owing to gender, with females outperforming males. Conclusions: The study found out that Arabic teachers play different roles in the classroom to different extents. Therefore, the study recommends providing a guide to help them understand the various classroom roles they are expected to perform. Additionally, it suggests conducting awareness lectures to enhance their social and emotional communication skills in the classroom, in line with the advancements of the digital age.